Modulation of T-Bet and GATA-3 expression in experimental autoimmune thyroiditis rats through ginsenoside treatment. (2nd January 2016) - Chen, Jie; Feng, Xiaohong; Huang, Qi
Abstract: Hashimoto's thyroiditis (HT) is one of the most common organ-specific autoimmune diseases. Increasing evidence indicates that HT may be characterized by an imbalance in the helper T cell subsets Th1 and Th2. Traditional Chinese Medicine (TCM) considers HT as a chronic exhaustion disease, leading to deficiency of qi. In TCM, qi indicates the functional power of the organs of the human body; hence TCM recommends focusing the treatment of HT so as to increase qi production. Ginseng is a well-known herbal medicine exhibiting a variety of efficacies, its main function-being to generate qi. Ginseng's principal active component is ginsenoside, and modern pharmacology has shown that ginsenoside demonstrates biphasic immunomodulatory effects that can be utilized for the treatment of immune disorders. Previous work demonstrated that ginsenoside has a therapeutic effect on HT, but its mechanism is unknown. Experimental autoimmune thyroiditis rats were produced in order to investigate whether ginsenoside can modulate Th1/Th2 imbalance, the direct objective being to examine modulation of IFN-γ and IL-4 by ELISA, and the gene and protein expression of T-bet and GATA-3 by real-time PCR and Western blot. IFN-γ levels were increased while IL-4 levels decreased in EAT rats; treatment with ginsenoside led to decreased peripheral blood IFN-γ levels, with low doses statistically significant. Ginsenoside produced a biphasic effect on IL-4, with low and moderate doses promoting and high doses inhibiting secretion. Both protein and mRNA levels of T-bet were markedly reduced, while GATA-3 was significantly increased by ginsenoside.